2016
DOI: 10.1002/aoc.3505
|View full text |Cite
|
Sign up to set email alerts
|

Natural hydroxyapatite‐supported MnO2: a green heterogeneous catalyst for selective aerobic oxidation of alkylarenes and alcohols

Abstract: Natural hydroxyapatite‐supported MnO2 (MnO2@NHAp) was easily prepared in situ from reduction of potassium permanganate with natural hydroxyapatite derived from cow bones in water at room temperature, and its structure was characterized using flame atomic absorption spectroscopy, X‐ray diffraction, thermogravimetric analysis, scanning electron microscopy and energy dispersive spectroscopy. The catalytic activity of the synthesized catalyst was investigated for the aerobic oxidation of alkylarenes and alcohols. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…01‐074‐0566) 28 . The obtained patterns are in agreement with Kim et al 29 and Heidari et al 30,31 MnO 2 peaks were also seen at angles of 18.20, 28.88, 35.46, 37.5, 41.97, 49.39, and 60.3° 26,32 . Given that the intensity of the peaks of the pattern of Figure 2B is greater than that of Figure 2A, it is concluded that the HA crystallinity increased by adding MnO 2 .…”
Section: Resultssupporting
confidence: 89%
“…01‐074‐0566) 28 . The obtained patterns are in agreement with Kim et al 29 and Heidari et al 30,31 MnO 2 peaks were also seen at angles of 18.20, 28.88, 35.46, 37.5, 41.97, 49.39, and 60.3° 26,32 . Given that the intensity of the peaks of the pattern of Figure 2B is greater than that of Figure 2A, it is concluded that the HA crystallinity increased by adding MnO 2 .…”
Section: Resultssupporting
confidence: 89%
“…[16][17][18][19][20][21][22][23][24] In particular,t heir oxidation catalysis is of great interest, and thus numerousa erobic oxidation systemst hat use catalysts based on manganese oxide have been developed. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] As fora lkylarene oxygenation, several catalysts based on manganese oxide have also been reported to be highly effective (Table S2); [40][41][42][43][44] for example, Hara and colleagues reported recently that nanosized hexagonal SrMnO 3 perovskite exhibits ah igh catalytic performance for alkylarene oxygenation under relatively mild conditions (60-120 8C, 1atm O 2 ,n oa dditives). [43,44] In this study,w ep repared heterogeneous catalysts based on manganese oxide for alkylarene oxygenation and we considered the following factors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the relatively high surface area and appropriate pore size of inorganic supports maintain their competitive advantages over others . Hydroxyapatite is a potentially useful material for designing new functionalized heterogeneous catalysts, because of its properties such as thermal and chemical stability, biocompatibility, adsorption capacity, high surface area and ionic substitution ability . Magnetic NPs, as nanotemplate and support for the synthesis of nanometric heterogeneous hosts for Ag NPs, provide quasi‐homogeneous reaction conditions.…”
Section: Introductionmentioning
confidence: 99%